Kāna Wa Akhawātuhā dalam Surat Al-Baqarah dan Kontribusinya dalam Pembelajaran Nahwu (Analisis Sintaksis) - Fikri Abdul Salam; Yusron Hidayat (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
This study investigates the occurrence and usage of kāna wa akhawātuhā (kāna and its sisters) in Surah Al-Baqarah, which comprises 286 verses. The researcher identified 88 instances of kāna wa akhawātuhā: 57 instances of kāna in the past tense (fi'il madli), 18 in the present tense (fi'il mudhari'), and 3 as imperative forms (fi'il amr). Additionally, there were 9 occurrences of laysa (fi'il madli) and 1 of mā zāla (fi'il mudhari'). The analysis categorized kāna wa akhawātuhā based on conditions of application, types of verbs, need for complements (khabar), and grammatical properties. Most forms acted without conditions, and the majority were complete in their inflection (kāmilut tashrif). Furthermore, the study explored the types of ism (subjects) and khabar (predicates) linked to kāna wa akhawātuhā, categorized by form, number, and gender. The findings provide a systematic inventory of kāna wa akhawātuhā examples, complete with parsing (i’rab) and detailed grammatical analysis, offering significant contributions for the teaching and learning of Arabic grammar (nahwu), particularly at the beginner and intermediate levels. The researcher also proposes instructional steps to integrate these findings into grammar learning practices.